1998
DOI: 10.1128/jcm.36.3.652-656.1998
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Study of a Food-Borne Outbreak of Enterotoxigenic Escherichia coli O25:NM by Pulsed-Field Gel Electrophoresis and Randomly Amplified Polymorphic DNA Analysis

Abstract: This study investigated the applicability of molecular epidemiological techniques to the identification of the causal agent of an outbreak of diarrhea caused by ingestion of food contaminated with enterotoxigenic Escherichia coli (ETEC). The outbreak occurred at four elementary schools in July 1996 and affected more than 800 people. Illness was most strongly associated with eating tuna paste (relative risk, 1.79; 95% confidence interval = 1.16 to 2.79; P = 0.0001). To evaluate the epidemiological characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…The strains isolated from the patients of foodpoisoning incidents in Tokyo and Kanazawa were identical as far as we determined. Furthermore, the strain reported by Mitsuda et al (12) showed the profiles of PFGE similar to those of the strains isolated in Tokyo and Kanazawa. One possibility deduced from these results is that the STIb-producing E. coli 025 strains derived from the same ancestor were spread and reproduced in Japan.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…The strains isolated from the patients of foodpoisoning incidents in Tokyo and Kanazawa were identical as far as we determined. Furthermore, the strain reported by Mitsuda et al (12) showed the profiles of PFGE similar to those of the strains isolated in Tokyo and Kanazawa. One possibility deduced from these results is that the STIb-producing E. coli 025 strains derived from the same ancestor were spread and reproduced in Japan.…”
Section: Discussionsupporting
confidence: 68%
“…One type of ETEC is E. coli which produces only ST. The outbreak of such E. coli infection in the primary schools in Yokohama in 1996 was recently reported by Mitsuda et al (12). The serotype of the strain was 025:NM, and it produced STIb (STIh).…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Consistent with our findings, strains of CS6 populate 15 of these lineages, indicating widespread genomic heterogeneity. PFGE has also been shown to be useful for outbreak [52,53] and nonoutbreak/surveillance of E. coli [54,55]. In this study we selected PFGE as the method for phylogenetic analysis, in part to create a database of ETEC isolates that would form the basis of the PulseNet Middle East E. coli system.…”
Section: Discussionmentioning
confidence: 99%
“…The contamination of fish with E. coli probably occurs during the insufficient handling of fish (Ayulo, Machado, & Scussel, 1994). An outbreak caused of diarrheal illness was reported in Japan, and it was associated with eating tuna paste, contaminated with enterotoxigenic E. coli (Mitsuda, Muto, Ito, & Yokota, 1998).…”
Section: Introductionmentioning
confidence: 99%